Transformasi Kurikulum Pendidikan Agama Islam Perkembangan Terkini dan Tantangan di Era Digital - Zaelani Zaelani; Junaidi Junaidi; Muhammad Muhammad; Muhsinin Muhsinin (Universitas Islam Negeri (UIN) Mataram, 2023)
Digital transformation in Islamic religious education offers great opportunities to increase the efficiency, effectiveness and quality of Islamic education. Some of these opportunities include using technology in learning, data management, and curriculum development. In the current digital era, educational institutions are required to be resilient in going through the challenges and changes that arise in people's lives to anticipate the negative impacts of the rapid progress of transformation. The development of technology and science that has occurred has resulted in some people taking advantage of opportunities and being able to make good use of them. For some people who are able to develop knowledge and give birth to new ideas and these ideas appear to answer the needs of society in various fields including in the world of education. This study uses the library research method or library research, which examines data sources with references to books or articles, previous research journals, and other scientific writings related to the theme of the transformation of Islamic religious education. The results of the study show that Islamic religious education is expected to be able to dig back capabilities in recognizing all the potential it has, then equip it with skills that are easy to understand so that it is able to interact with the digitalization era. Keywords: Curriculum transformation, Islamic religious education Transformasi digital dalam pendidikan agama Islam menawarkan peluang besar untuk meningkatkan efisiensi, efektivitas, dan kualitas pendidikan Islam. Beberapa peluang ini meliputi penggunaan teknologi dalam pembelajaran, manajemen data, dan pengembangan kurikulum. Pada era digital saat ini lembaga pendidikan dituntut tangguh dalam melewati tantangan dan perubahan yang muncul di dalam kehidupan masyarakat untuk mengantisipasi dampak negatif dari kemajuan transformasi yang begitu cepat. Perkembangan teknologi dan ilmu pengetahuan yang telah terjadi mengakibatkan sebagian orang mengambil kesempatan dan mampu memanfaatkannya dengan baik. Bagi sebagian orang yang mampu mengembangan ilmu pengetahuan dan melahirkan gagasan baru dan gagasan ini muncul untuk menjawab kebutuhan masyarakat dalam berbagai bidang termasuk juga dalam dunia pendidikan. Penelitian ini menggunakan metode library research atau studi kepustakaan yaitu mengkaji sumber data dengan rujukan buku-buku atau artikel, jurnal penelitian sebelumnya, dan tulisan ilmiah lainnya yang berkaitan dengan tema transformasi pendidikan agama islam. Hasil penelitian menunjukan bahwa Pendidikan agama islam diharapkan mampu menggali kembali kapabilitas dalam mengenali segala potensi yang dimiliki, lalu membekalinya dengan keterampilan yang mudah dipahami sehingga mampu berinteraksi dengan era digitalisasi. Kata kunci: Transformasi kurikulum, pendidikan agama Islam